Le palmier dattier (Phoenix dactylifera L.) dans l’Arabie méridionale préislamique - Jérémie Schiettecatte (Revue d'ethnoécologie)
This paper deals with the date palm tree culture in pre-Islamic South Arabia, from its beginning until the 6th century AD. Crossing archaeobotanical data and epigraphic mentions of the date palm made it possible to draw up a diachronic map of ancient palm groves. This in turn served as a basis to discuss the issue of the origin and diffusion of the date palm culture at a regional scale: where and when did it begin? How did it spread? And what place did it take in the society, as foodstuff or as a symbol? It seems that this culture appeared only late in the region. It was mainly limited to the lower valleys of the inland and was not a long-lasting culture of South Arabia.